Research on the Circulation and Evolution of Fonts in Dunhuang Manuscripts from the Perspective of Calligraphy Art (Journal of Global Arts Studies, 2025)
Background: In 1900, the Library Cave of the Mogao Caves in Dunhuang was discovered, revealing more than 50,000 manuscripts, including calligraphy works, Buddhist scriptures, and stele rubbings. Together with oracle-bone inscriptions, Dunhuang manuscripts are regarded as one of the “Four Great Academic Discoveries” of modern China. Spanning more than seven centuries, these documents embody rich historical and cultural significance. Objective: From the perspective of calligraphy history, this paper aims to examine the evolution of calligraphic styles, the inheritance and transformation of artistic traditions, as well as the fusion of styles and the development of brushwork techniques from the late Jin Dynasty to the early Song Dynasty. Method: This study conducts a qualitative analysis of a large number of Dunhuang unearthed documents, including Buddhist scriptures, letter-writing manuals, copies of Wang Xizhi’s works, Tang Dynasty stele rubbings, and fragments of calligraphy theory. Results: The findings show that Buddhist scriptures and letter-writing manuals constitute a major portion of the Dunhuang manuscripts, presenting a relatively complete trajectory of the evolution of scripture-copying styles. The manuscripts encompass all major calligraphic scripts, demonstrating stylistic diversity and a wide variety of artistic forms. Conclusion: Dunhuang manuscripts are of irreplaceable value for the study of Chinese calligraphy history. Their calligraphic works possess a distinctive and natural aesthetic character, forming an independent artistic system with strong regional features. At the same time, they maintain close connections with the calligraphic traditions of the Central Plains and Jiangnan regions, making them an indispensable part of ancient Chinese calligraphy history.
Keywords: Dunhuang Manuscripts; The Evolution of Calligraphy; History of Calligraphy; Aesthetic Taste